HUBUNGAN ANTARA KONSEP DIRI DENGAN MOTIVASI BERPRESTASI PESERTA DIDIK DI SMA NEGERI I KECAMATAN KAPUR IX KABUPATEN LIMA PULUH KOTA - Sari, Reski Puspita; Kasih, Fitria; Nofrita, Nofrita (Bimbingan dan Konseling, 2013)
Achievement motivation is influenced by several factors, one of which is the concept of self. This study aims to determine whether there is a relationship between self-concept and achievement motivation of students in Senior High School 1 Kecamatan Kapur IX Kabupaten Lima Puluh Kota. This reseach is a quantitative correlation is the relationship between self-concept and achievement motivation of students in Senior High School 1 Kecamatan Kapur IX Kabupaten Lima Puluh Kota. The study population numbered 329 people who registered the 2012-2013 school year, with a total sample of 77 people were taken using random sampling techniques sratified. Collecting data using questionnaires about self-concept and achievement motivation. The data obtained were analyzed using percentage formula. Results of research conducted can be described as follows: 1) students in Senior High School 1 District 50 District IX Limestone City has a good self-concept, 2) learners at SMA Negeri 1 Kecamatan Kapur IX Kabupaten Lima Puluh Kota has a good achievement motivation, 3 ) there is a significant relationship between self-concept and achievement motivation of learners in SMA Negeri 1 Kecamatan Kapur IX Kabupaten Lima Puluh Kota with countÂ of 0.410 at a significance level of 0.00 and r table is 0.227. Based on the findings of this study are expected to guidance and conceling teachers to be able to design a program appropriate services for students in the handling of issues related to self-concept and improve student achievement motivation in learning.